2022
DOI: 10.1145/3498725
|View full text |Cite
|
Sign up to set email alerts
|

Software model-checking as cyclic-proof search

Abstract: This paper shows that a variety of software model-checking algorithms can be seen as proof-search strategies for a non-standard proof system, known as a cyclic proof system . Our use of the cyclic proof system as a logical foundation of software model checking enables us to compare different algorithms, to reconstruct well-known algorithms from a few simple principles, and to obtain soundness proofs of algorithms for free. Among others, we show the significance of a heuristics based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Since, in general, we cannot expect there to be any syntactical relationship between the node and its ancestor, the formation of cycles is closely related to the use of cuts in the proof. Indeed Tsukada and Unno [52] have demonstrated that many techniques developed for efficient software model checking can be viewed as the introduction of cuts into cyclic proofs to discharge proof obligations earlier.…”
Section: Cyclic Proofs and Equational Reasoningmentioning
confidence: 99%
See 1 more Smart Citation
“…Since, in general, we cannot expect there to be any syntactical relationship between the node and its ancestor, the formation of cycles is closely related to the use of cuts in the proof. Indeed Tsukada and Unno [52] have demonstrated that many techniques developed for efficient software model checking can be viewed as the introduction of cuts into cyclic proofs to discharge proof obligations earlier.…”
Section: Cyclic Proofs and Equational Reasoningmentioning
confidence: 99%
“…Specifically, a cyclic proof system for separation logic has been given that automatically verifies that a program terminates [8,51]. Cyclic proof systems have recently been shown to subsume generic model-checking algorithms such as: lazy-abstraction with interpolants, property-directed reachability, and maximal conservativity for infinite game solving [52]. As with the generic cyclic theorem prover Cyclist, it is the choice of "matching-function" or "cut" that determines exactly how the verification algorithm operates outside of the usual reasoning on the abstract domain.…”
Section: Related Work and Conclusionmentioning
confidence: 99%
“…However, Saotome [14] suggested that there still exist sequents in the symbolic heap separation logic that cannot be found by a normal proof search procedure admitting (Cut) whose cut formulas are presumable from the goal sequent. Recently the framework of cyclic proof-search has been studied from the viewpoint of software verification [20,21].…”
Section: Introductionmentioning
confidence: 99%